2010
DOI: 10.1007/s00404-010-1499-9
|View full text |Cite
|
Sign up to set email alerts
|

94 months follow-up after laparoscopic assisted vaginal resection of septum rectovaginale and rectosigmoid in women with deep infiltrating endometriosis

Abstract: Despite the small number of follow-up patients, our 94-month follow-up data demonstrated that endometriosis with bowel involvement and radical resection was associated with significant reductions in painful and dysfunctional symptoms, a low recurrence rate (6.6%) and high pregnancy rate (36.6%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 23 publications
5
30
0
2
Order By: Relevance
“… performed laparoscopic segmental colorectal resection in all patients, whereas Kavalleris et al. used a combined laparoscopic and vaginal approach for en bloc resection of the affected bowel segment, cul de sac, rectovaginal septum and vaginal wall. Meuleman et al.…”
Section: Resultsmentioning
confidence: 99%
“… performed laparoscopic segmental colorectal resection in all patients, whereas Kavalleris et al. used a combined laparoscopic and vaginal approach for en bloc resection of the affected bowel segment, cul de sac, rectovaginal septum and vaginal wall. Meuleman et al.…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, they noted that the possibility of treating peritoneal and ovarian endometriomas without excising the rectovaginal plaques should be considered, particularly in women with limited pain. However, a growing body of literature describes colorectal resection for severe endometriosis,1015 particularly procedures involving a laparoscopically assisted technique. Meanwhile, others16 suggest that a laparoscopic resection of rectovaginal endometriosis may be associated with a higher incidence of complications than resection performed for other diagnoses.…”
Section: Discussionmentioning
confidence: 99%
“…In a literature review of VD in patients with DIE, Bonneau et al reported that the rate of persistent VD ranges from 0% to 14.7% with a mean value of 4.6% (66/1430 patients) [7]. In a prospective study of 55 patients undergoing en bloc rectovaginal septum resection with a median follow-up of 94 months, Kavallaris et al observed that among 14 patients with postoperative VD only two required self-catheterization over a year [20]. Similarly, Benbara et al confirmed that only 2% of patients required self-catheterization over a year after surgery [21].…”
Section: Commentsmentioning
confidence: 98%